MENINGKATKAN KEMAMPUAN MENULIS KALIMAT MELALUI MEDIA GAMBAR BAGI ANAK TUNARUNGU - Fitri Handayani; Ganda Sumekar; Kasiyati - (Universitas Negeri Padang, 2013)
Abstrack: This study originated from research results of the assessment carried out in SLBN II Pariaman, where X deaf children aged 11 years has not been able to write a sentence composed. Accordingly, this study was done so that the deaf children can write sentences are structured. In the research hypothesis stated that: media images can improve the ability to write a sentence for deaf children in the third grade II cottage SLB N 20 Pariaman. This research uses experimental research in the form of Single Subject Research (SSR) with the AB design. Subjects were children with hearing X class III (three). The target behavior in this study is children's ability to write a sentence, judgment was given in the form percentage (%). This research was first seen from the baseline condition in the child's ability to write sentences beginning. This was followed in the intervention condition condition continued to be treated. The data obtained were processed with graphs. So the results of this study can be illustrated by this study suggests that jelas.Hasil, media images can improve children's ability to write a sentence, it can be seen in the baseline phase in which the child is not able to answer ten questions about writing sentences. Thus the hypothesis is accepted that media images can improve the ability to write sentences for third grade deaf children in special school N 20 Cottage II Pariaman. Teachers and researchers suggest further research in order to provide learning by using media images to write sentences in future learning. Kata Kunci: Menulis Kalimat; media gambar; anak tunagrahita